The Perception of Climate Change: the Hill Ecology and the People in India - Acharya, SK (Journal of Agricultural Extension Management, 2019)
The brunt of climate change on the hill ecosystem is very conspicuous and discernible across the world. The melting of the snow cover, the rise of mean temperature, the loss of biodiversity etc, are the evidences of imminent losses and deleterious impact on agriculture, human life and biodiversity which may be elicited as social ecology. In the present study, the Hill ecosystem of North Sikkim has been selected as a research locale to estimate the people’s perception on the impact of climate change on this fragile ecosystem. The variables Y (Climate change perception), Y2 (Yield change perception), Y3 (Water bodies perception), Y4 (Health problem perception), Y5 (Species decline perception), Y6Â (Perception indicator change), Y7 (Landslide perception), Y8 (Distance perception), Y (Comprehensive climate change perception) have been selected and customised as core of Predictants, against which the variables X1Â (Age), X2 (Education), X3 (Family size), X4 (Media interaction), X5 (Per capita holding size), X6 (Cropping intensity), X7 (Technology socialization status), X8 (Family income), X9 (Expenditure on health), X10Â (Animal health mentoring), X11Â (Location of the market), have been selected as having causal impact on the above stated perceptual variables. It has been found that the variable X2 (Education) has got decisive impact on climate change perception, while path analysis has revealed that the variable X3 (Family size) has exerted the HIDE (Highest Indirect Effect) on climate change perception. The correlation analysis has evinced that the variables X2 (Education), X6 (Cropping intensity), X8 (Family income), have been significantly correlated with climate change perception. Canonical correlation analysis has been conducted to determine whether two set of variables are independent of one another or conversely determining the magnitude of the relationship.